The Little Green Data Book 2016 - World Bank (Washington, DC: World Bank, 2016)
The Little Green Data Book 2016 is a pocket-sized ready reference on key environmental data for over 200 countries. Key indicators are organized under the headings of agriculture, forestry, biodiversity, oceans, energy, emission and pollution, and water and sanitation.